2011
DOI: 10.1007/s11199-011-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Rape Myths and Sexual Scripts: The Social Construction of Rape

Abstract: Rape myths can influence sexual scripts that determine sexual attitudes and behavior. Sexual scripts are culturally determined patterns of behavior that inform desire and influence sexual behavior. Sexual scripts include hook up, seduction, rape, and acquaintance rape scripts (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(163 citation statements)
references
References 53 publications
6
152
1
4
Order By: Relevance
“…The relation between RMA and labeling may be explained by the substantial overlap in stereotypical beliefs between rape myths and rape scripts (Edwards, Turchik, Dardis, Reynolds, & Gidycz, 2011;Ryan, 2011), given that interpretations and assigned labels of acts of sexual violence are influenced by rape scripts and other stereotypical beliefs, which are common features of rape myths. The exploratory qualitative findings are consistent with these results, as the most common reasons for labeling the vignette as a rape were those that are strongly associated with stereotypical rape (i.e., lack of consent, use of force).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation between RMA and labeling may be explained by the substantial overlap in stereotypical beliefs between rape myths and rape scripts (Edwards, Turchik, Dardis, Reynolds, & Gidycz, 2011;Ryan, 2011), given that interpretations and assigned labels of acts of sexual violence are influenced by rape scripts and other stereotypical beliefs, which are common features of rape myths. The exploratory qualitative findings are consistent with these results, as the most common reasons for labeling the vignette as a rape were those that are strongly associated with stereotypical rape (i.e., lack of consent, use of force).…”
Section: Discussionmentioning
confidence: 99%
“…This conceptualization has been termed "stereotypical rape," and recent studies have shown that individuals continue to have stereotypical scripts of what constitutes a "real" or "legitimate" rape, including features such as the perpetrator's use of physical force and the victim's use of physical resistance (see Ryan, 2011 for a review). Unfortunately, this view puts an overly restrictive framework around victims' experiences, which do not usually conform to this stereotype (e.g., Koss, Heise, & Russo, 1994;Littleton, Tabernik, Canelas, & Backstrom, 2009).…”
Section: Labeling Sexual Violencementioning
confidence: 99%
“…Another interesting discourse analytical study investigated how sexual scripts occur in conversation, and how these are related to rape myths; the findings of which demonstrated that sexual scripts determine the social construction and support of rape (Ryan, 2011).…”
Section: New Methodologiesmentioning
confidence: 99%
“…Although there has been some movement in this direction (Abbey, 2002), and guidance offered by the Center for Disease Control (Basile, Smith, Breiding, Black & Mahendra, 2014), there are still a variety of definitions and instruments used in current literature on sexual assault. This diversity in definitions is further complicated by variations from professional fields such as medical, legal, (Teurkheimer, 2015) and research (Bagwell, Messing, Baldwin-White, 2015), which may exacerbate college student uncertainty of what constitutes sexual assault (Ryan, 2011). The US Department of Justice recently hosted an expert panel on how best to measure sexual assault, which is an important next step in leading researchers to a more integrated and universal method of measurement in the future (Kruttschnitt, Kalsbeek & House, 2013).…”
Section: Areas For Future Researchmentioning
confidence: 99%